Memanfaatkan Teknologi Informasi Dalam Mewujudkan Good Governance Di Pemerintahan Kota Batam - Nova, Rahma Desi Refli; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
This article highlights the importance of using information technology to achieve good governance in Batam City government. Transparency, accountability, public participation, and efficiency in government are all components of good governance. The use of information technology can encourage transparency by making government data and information more easily accessible. In addition, information technology increases accountability by providing an electronic reporting system that is accurate and timely. Digital systems that enable online public participation increase public participation. Instagram, Twitter, and Facebook are examples of online social media that are currently very easy to access. Mass media, such as advertisements, banners, billboards and pamphlets, are another type of information delivery medium. The method used in this scientific article is data analysis. The material provided in this topic is communicated through a descriptive approach by directing or indirectly using various intermediary media. Online intermediaries are really needed by the government to reach all communities now and for future prospects. Online intermediary media is the most perfect media to reach all levels of society. By using technology to automate administrative tasks, information technology increases efficiency. The use of information technology in the Batam City government is a strategic step towards creating a more open, accountable, responsive and efficient government which is expected to benefit all the people of Batam City